2019
DOI: 10.1021/acs.jpcc.9b03957
|View full text |Cite
|
Sign up to set email alerts
|

Formation of AlFx Gaseous Phases during High Temperature Etching: A Reactive Force Field Based Molecular Dynamics Study

Abstract: The progress of research focused upon the etching of metal films or substrates using fluorine gases has been restricted by limited information regarding etching reactants and byproducts. Indeed, aspects of the etching mechanism itself remain unclear. In this study, a new reactive force field (ReaxFF) for Al−F was developed to describe the interaction and reactions in Al−F materials. The ReaxFF accurately reproduces the quantum mechanics derived training set for structures and energies of gaseous AlF x molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…These calculations provide another avenue of explanation of why etching of alumina is more difficult than aluminum. Liu et al 16 conducted a molecular dynamic study on the formation of AlF 3 from bulk Al and F 2 molecules. They have reported the formation of AlF 3 at temperatures 1000−1500 K. Such a high temperature requirement may result from the fact that they considered Al bulk.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These calculations provide another avenue of explanation of why etching of alumina is more difficult than aluminum. Liu et al 16 conducted a molecular dynamic study on the formation of AlF 3 from bulk Al and F 2 molecules. They have reported the formation of AlF 3 at temperatures 1000−1500 K. Such a high temperature requirement may result from the fact that they considered Al bulk.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…More specifically, it is not known how aluminum interacts differently than alumina, whether the neutral F atom or F 2 molecules interact with aluminum/alumina, the role of IPA, etc. More recently, Liu and co-workers 16 presented a force field molecular dynamic study on the formation of AlF x from aluminum and F 2 gas. They reported that various AlF x were formed from aluminum and F 2 gas at 1000−1500 K, which are well above the plasma operation temperature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…ReaxFF potential developed by Liu et al 13 was used to describe the kinetics and reactivity characteristics of F and O adatoms on the Al(111) surface. The Al(111) surface was modeled by 8 Â 8-15 layer supercells.…”
Section: Reactive Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Their results identify that there is a stable and nonvolatile layer of AlF 3 on the Al 2 O 3 surface, indicating that this reaction is self-limiting. Liu et al 13 studied the effects of the chemical source and temperature (1000–1500 K) on the etching product and etching rate by reactive force field (ReaxFF) based molecular dynamics (RMD). When the concentration ratio of F over Al is lower than three, the gaseous species cannot be formed; above this concentration, AlF 4 , AlF 5 and AlF 6 gaseous phases will be formed.…”
Section: Introductionmentioning
confidence: 99%